Using Nvivo to Analyze the Impact of Computer Simulation of Parent-Child Cooperative Art Activities on the Growth of Preschool Children. - Xie, En; Wong, Shaw-chiang; Bai, Ying (Journal of Autism & Developmental Disorders, 2024)
Psychology originally defined parent–child conflict in terms of interpersonal relationships, where parent–child conflict is a process of inconsistent attitudes between parents and children that occurs in a family setting. For this end, we aims to investigate the influence of parental awareness on preschoolers' perception of parent–child conflict and the mediating role of preschoolers' self-esteem. This paper proposes a dynamic parent–child relationship discovery algorithm based on the impact of parent–child cooperation activities on preschool children's development. We applied SPSS and Mplus statistical software for data processing and analysis, and Nvivo 11.0 qualitative software for validation and analysis. The reliability of preschool children's perceived parent–child conflict and sub-dimensions were: 0.901, 0.799, 0.791, 0.811, 0.729; the total scale and the retest reliability of each dimension were: 0.914, 0.837, 0.836, 0.792, 0.711. Validated factor analysis using Mplus: RMSEA = 0.075, TLI = 0.856, CFI = 0.876, SRMR = 0.064.